VARIATION IN THYROID ACTIVITY WITH RESPECT TO ANNUAL SEASONAL CYCLE OF REPRODUCTION IN TURTLE MELANOCHELYS TRIJUGA : Life Science-Spectroscopy - R. CHANDAVAR, VIDYA.; R. NAIK, PRAKASH. (International Journal of Life Science and Pharma Research, 2012)
The present investigation was carried out to find out the relationship between annual cycle of reproduction and thyroid activity in Melanochelys trijuga. The animals were studied in the annual seasonal cycle of reproduction which is distinguished into three separate periods namely regenerative, reproductive and recrudescent. Thyroid is an unpaired, oval shaped gland. Paraffin embedded thyroid sections were studied by bromophenol blue method for thyroglobulin. Liver sections were localized for glycogen. Plasma glucose was estimated in different periods of reproductive cycle. Thyroid showed seasonal variation in its activity. The present investigation demonstrates increased thyroid activity from regenerative to reproductive period which decreased to minimum in recrudescent period. The active thyroids appeared spongy and translucent with maximum weight and size. Weight of the gland is positively correlated with weight of the animal. Liver glycogen and abdominal fat was utilized during winter months of recrudescent period to maintain basal metabolic rate. Environmental temperature appeared to play effective role on thyroid activity. Cyclic changes in the thyroid may have indirect effect on reproductive cycle, sexual behaviour as well as in gonad maturation.